2012
DOI: 10.1007/s00380-012-0250-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inflammatory response after implantation of sirolimus- and paclitaxel-eluting stents in patients on hemodialysis

Abstract: Because systemic inflammation after coronary intervention places patients at increased risk of subsequent cardiac events, we aimed to compare clinical outcomes and chronic serum inflammation markers of paclitaxel-eluting stents (PES) and sirolimus-eluting stents (SES) in hemodialysis patients. Paclitaxel-eluting stents and SES were implanted in 36 patients with 46 lesions, and 32 patients with 40 lesions, respectively. In addition to 1-year major adverse cardiac event (MACE) rates, high-sensitivity C-reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Calabró et al [34] reported that IL-1β and IL-6 stimulated CRP production in cultured human coronary artery smooth muscle cells. The concentrations of IL-1β and IL-6 used in their experiments were also more than 1,000 times that of the PCI-associated pathophysiological ranges detected in our study and others [32]. VSMCs in vessels induced by inflammatory cytokines at the PCI-associated pathophysiological range were not able to express CRP.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Calabró et al [34] reported that IL-1β and IL-6 stimulated CRP production in cultured human coronary artery smooth muscle cells. The concentrations of IL-1β and IL-6 used in their experiments were also more than 1,000 times that of the PCI-associated pathophysiological ranges detected in our study and others [32]. VSMCs in vessels induced by inflammatory cytokines at the PCI-associated pathophysiological range were not able to express CRP.…”
Section: Discussionmentioning
confidence: 82%
“…This indicates that the coronary arteries with stent implantation do not seem to produce many inflammatory markers. This phenomenon might be the result of the local inhibition effect of rapamycin (in the stent) on the vessel, or due to the stent encapsulating completely or partially with connective tissue and endothelial cells [32,33]. Acute inflammation (including noninfectious inflammation) from PCI increases the secretion of the cytokines IL-6 and IL-1β, which in turn encourage CRP expression mainly in the liver through different signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pencak et al [8] suggested that the time on HD therapy (per year) was an independent risk factor that favored the occurrence of coronary artery calcification by the computed tomography assessment, and in our data, the calcified lesions were more frequently observed in the long HD duration group. Several mechanisms such as disturbances in mineral metabolism, oxidative stress, inflammation, and neoangiogenesis have been recognized as causes of atherosclerosis progression in HD patients [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Yano et al. published a small study where they were looking at inflammatory markers after implantation of PES and SES in hemodialysis population . They showed that high‐sensitivity C‐reactive protein (hs‐CRP) as well as interleukin 6 (IL‐6) decreased significantly post‐PES implantation, but not after SES.…”
Section: Discussionmentioning
confidence: 99%